5,6-dihydroxyflavone exerts anti-betacoronavirus activity by blocking viral entry to host cells - Yujia Cao; Kah Man Lai; Hongling Zheng; Yee Joo Tan; Dejian Huang (Virus Research)
Baicalin, a bioactive flavone found in Scutellaria baicalensis Georgi has anti-SARS-CoV-2 infection by targeting viral 3C-like protease (3CLpro). However, little is known about the antiviral activity of its 7-deoxy analogue, 5,6-dihydroxyflavone (5,6-DHF), especially against betacoronaviruses (beta-CoVs). We found that 5,6-DHF exhibited more potent anti-SARS-CoV-2 Omicron variant EG.5.1.1 activity than baicalein by microneutralization test (MNT) and plaque reduction neutralization test (PRNT). 5,6-Dihydroxyl (catechol) groups at A ring of 5,6-DHF is essential for its suppression on SARS-CoV-2 Omicron variant EG.5.1.1 infection because blocking them with methyl or methylene groups obsolesce the activity. 3CLpro inhibition assay showed that the antiviral activity of 5,6-DHF is distinctive with baicalein. Time of addition test, molecular docking and spike-bearing pseudotyped virus entry assay suggested that 5,6-DHF interferes the spike-ACE2 interaction by targeting at receptor binding domain (RBD) of spike and hence inhibits the virus replication. In addition to SARS-CoV-2 Omicron variant EG.5.1.1, 5,6-DHF was also found effective against another common human beta-CoVs, HCoV-OC43, by blocking their entry to host cells. Taken together, the present study demonstrated the potential function of 5,6-DHF as a therapeutic candidate against beta-CoVs.